THE EFFICIENCY OF FINANCIAL RATIOS IN PREDICTING THE FINANCIAL SUCCESS OR FAILURE OF FINANCIAL INSTITUTIONS-AN ANALYTICAL STUDY OF THE BANK OF BAGHDAD (World Economics and Finance Bulletin, 2024)
The research aims to demonstrate the efficiency of financial ratios in predicting the success or failure of financial institutions and the impact of credit risks to which the banks of the study sample are exposed to on granting loans and credit facilities, and to attempt to reduce the amount of credit risks to which banks are exposed as a result of granting loans and credit facilities, as credit risk is the oldest form It is a form of risk in the financial markets, and all banks bear a degree of risk when they grant loans and credit facilities to companies and customers, as they are exposed to financial losses when some borrowers fail to repay their loans as agreed upon. At the same time, credit facilities are the most profitable operations for the bank, as they are the most profitable banking operations. Income from other banking operations. The research population was represented by banks listed on the Iraq Stock Exchange, while the research sample was represented by the Bank of Baghdad, for the period (2017-2022), and a set of financial indicators were used (total debt ratio, capital adequacy ratio, debt-to-equity ratio, and loan-to-equity ratio). Current assets, the rate of provision for loan losses, and the ratio of loans to deposits) to measure the research variables and test the research hypotheses. The research concluded that there is no statistically significant effect of credit risk indicators on loans and credit facilities in general, but there is a partial effect of some credit risk indicators. On indicators of loans and credit facilities.